Diskurslinguistik nach Foucault: Theorie und Gegenstände - Warnke, Ingo H. (Linguistik - Impulse & Tendenzen, 2007)
Biographical note: Ingo H. Warnke, Universität Kassel
Includes bibliographical references and index
Papers presented at a conference held autumn 2004, Kassel, Germany
Keywords: Foucault, Michel -- 1926-1984 -- Congresses; Konferenzschrift -- 2004 -- Kassel; Linguistik; Diskurstheorie